"I was able to ask for help when I became stressed rather than sitting alone and struggling": psychology and law students' views of the impact of identity and community on mental wellbeing. Issue 1 (2nd January 2022) - Fay, Michael; Skipper, Yvonne
ABSTRACT: People derive a sense of self from membership of social groups. Universities consist of many different groups and provide a significant opportunity to explore how group memberships can affect mental wellbeing. A key university group is students' school of study, membership of which enables individuals to develop an academic identity. We argue that a strong sense of belonging, and thus academic identity, within the school community can lead to positive mental wellbeing. We focus on belonging within academic schools because the positive impact of group membership is likely to exist to a greater degree in an academic school than in other university communities. We conducted online focus groups with 21 undergraduate students studying either law or psychology at a research-intensive university. Our aim was to explore their academic identity and belonging within their academic school of study, and how these variables affected their mental wellbeing. Our thematic analysis indicates that students with strong identities, who feel a sense of belonging in their school community – particularly among peers – display greater help-seeking behaviours in difficult times. If peers are viewed negatively, students are less forthcoming when in need of support. Promoting peer support is therefore a way of improving student mental wellbeing.